Efek Penambahan Diethanolamine dan Suhu Kalsinasi terhadap Energi Gap Lapisan Tipis CuSnO3 - Sukma, Vira Ananda; Sanjaya, Hary (Asian Journal of Science, Technology, Engineering, and Art, 2023)
This study focuses on the synthesis of CuSnO3 thin films using the sol-gel dip coating method, with a particular emphasis on the effects of diethanolamine (DEA) addition and calcination temperature on the bandgap energy. The successful addition of DEA significantly influenced the reduction of the bandgap energy of CuSnO3 thin films, decreasing from 3.21 eV (without DEA) to 2.11 eV (optimal DEA addition, 1.5 mL), as characterized by UV-DRS. Furthermore, different calcination temperatures yielded varying bandgap energies, with the lowest bandgap energy observed in samples calcined at 550°C. This research provides valuable insights into the manipulation of CuSnO3 thin film properties for potential applications in optoelectronic devices and other emerging technologies.